ChemInform Abstract: Synthetic α‐(Aminomethyl)‐γ‐butyrolactones and Their anti‐Pancreatic Cancer Activities. Issue 20 (20th May 2014) - Ramachandran, P. Veeraraghavan; Nicponski, Daniel R.; Nair, Hari N.G.; Helppi, Matthew A.; Gagare, Pravin D.; Schmidt, C. Max; Yip‐Schneider, Michele T.
Abstract A variety of aminolactones such as (III) are synthesized which exhibit excellent activities against three pancreatic cancer cell lines